Competition, contracting and cost–sharing in the NHS internal market. (4th August 2014) - Gray, Keith E.; Ghosh, Deb
The NHS Internal Market provided a testing ground for some hypotheses on relationship building between purchasers and providers of secondary health care. An empirical analysis is presented based upon a major survey of NHS Trusts. LOGIT models were used to tackle the qualitative nature of a series of different hypotheses relating to competing MIS Trusts and their risk avoidance strategies. Furthermore, the analysis has been extended to estimate the prevalence of risk avoidance strategies for any specific local health market scenario. The results also enabled some predictions regarding the impact of recent NHS reforms on the relationship building phenomenon.